The trial of Galileo, 1612-1633 - Mayer, Thomas F. (Thomas Frederick), 1951-2014 (North York, Ontario : University of Toronto Press, 2012)
Examines Galileo's trial as a legal event. Includes correspondence, legal documents, transcripts and excerpts from Galileo's work for critical analysis of primary sources. Includes an introduction detailing Galileo's life and work, the Council of Trent, the role of the papacy and the Roman Inquisition and gives a clear explanation of how a trial before the Inquisition would have been conducted. Each primary source begins with a headnote, questions to guide students through each source and suggested readings.
Sunspot Letters : the cause of most of the trouble -- Formal proceedings begin -- The Inquisition and the Index take action -- Publication to Dialogue on the two chief world systems and the beginning of the trial's second phase -- Summons to Rome and Galileo's resistance -- Galileo arrives in Rome -- Formal proceedings resume -- Sentence and abjuration.
Primary source material translated from the Latin.
Includes bibliographical references and index.
Added to collection customer.56279.3
Keywords: Galilei, Galileo, -- 1564-1642 -- Trials, litigation, etc. -- Early works to 1800 -- Sources; Catholic Church -- Doctrines -- History -- Early works to 1800 -- Sources; Galilei, Galileo, -- 1564-1642.; Catholic Church; Trials (Heresy) -- Italy -- Rome -- History -- Early works to 1800 -- Sources; Inquisition -- Italy -- Rome -- Early works to 1800 -- Sources; Religion and science -- History -- Early works to 1800 -- Sources; Astronomers -- Italy -- Biography -- Early works to 1800 -- Sources; HISTORY / Modern / 17th Century; Astronomers -- Italy -- Biography -- Early works to 1800 -- Sources; Catholic Church -- Doctrines -- History -- Early works to 1800 -- Sources; Galilei, Galileo, -- 1564-1642 -- Trials, litigation, etc. -- Early works to 1800 -- Sources; Inquisition -- Italy -- Rome -- Early works to 1800 -- Sources; Religion and science -- History -- Early works to 1800 -- Sources; Trials (Heresy) -- Italy -- Rome -- History -- Early works to 1800 -- Sources; Astronomers; Inquisition; Religion and science; Theology, Doctrinal; Trials; Trials (Heresy); Italy; Italy -- Rome; Electronic books; History